2010
DOI: 10.1103/physrevb.82.134111
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility of cubic white, orthorhombic black, rhombohedral black, and simple cubic black phosphorus

Abstract: The effect of pressure on the crystal structure of white phosphorus has been studied up to 22.4 GPa. The α phase was found to transform into the α' phase at 0.87 ± 0.04 GPa with a volume change of 0.1 ± 0.3 cc/mol. A fit of a second order BirchMurnaghan equation to the data gave Vo = 16.94 ± 0.08 cc/mol and K o = 6.7 ± 0.5 GPa for the α phase and Vo = 16.4 ± 0.1 cc/mol and K o = 9.1 ± 0.3 GPa for the α' phase. The α' phase was found to transform to the A17 phase of black phosphorus at 2.68 ± 0.34 GPa and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 25 publications
(33 reference statements)
4
35
0
Order By: Relevance
“…When a negative pressure derivative is derived through parameterization of an EOS model, it usually is an indication that stress is being reduced through a structural phase transition where mixed crystalline phases co-exist or because there is an ensuing isostructural phase transition. (Isostructural transitions are often subtle and difficult to identify in P-V plotted data; discontinuous changes to pressure dependent cell volumes can be on the order of 1% or less than the experimental error 40 ). Analysis of the AlF 3 diffraction data indicates that the latter process occurred.…”
Section: A Alfmentioning
confidence: 98%
“…When a negative pressure derivative is derived through parameterization of an EOS model, it usually is an indication that stress is being reduced through a structural phase transition where mixed crystalline phases co-exist or because there is an ensuing isostructural phase transition. (Isostructural transitions are often subtle and difficult to identify in P-V plotted data; discontinuous changes to pressure dependent cell volumes can be on the order of 1% or less than the experimental error 40 ). Analysis of the AlF 3 diffraction data indicates that the latter process occurred.…”
Section: A Alfmentioning
confidence: 98%
“…Transition temperature is almost independent with temperature. [31][32] This simple cubic phase keeps stable even the pressure is increased up to 60 GPa. [33] …”
Section: Crystal Structurementioning
confidence: 99%
“…19,[23][24][25][26][27][28][29][30][31] Recently, Du et al 32 performed calculations for single layered and bulk black phosphorus and reported that black phosphorus may be used as anode material for lithium ion batteries.…”
mentioning
confidence: 99%